Risk factors and prognosis of some actual congenital infections - S. Kh. Kuyumch’yan; V. V. Vasil’ev; N. P. Alekseeva (Журнал инфектологии, 2016)
Purpose: modeling the risk of congenital infections (СI) based on a comprehensive assessment of the results of laboratory monitoring of pregnant women and infants. Materials and techniques: The study involved 92 pregnant women and 41 children born to them. A survey of pregnant women included the collection of standard anamnestic data and a set of laboratory diagnostic measures to identify markers of rubella, toxoplasmosis, herpes virus, cytomegalovirus, parvovirus B19V, chlamydia, mycoplasma, ureaplasma, assessment of the mucosa of the cervix in the first, second and third trimesters. Dynamic observation of children participating in the study included an assessment of somatic and neurological status, enzime-linked immunosorbent assay of blood serum for CI markers, molecular-genetic studies of blood. Results: using the methods of discriminant and regulate discriminant analysis, two groups of aggregated factors identified as having a significant impact on the development of CI, regardless of its etiology. The greatest weight for the prediction of congenital infections were immune status of pregnant towards herpes and the appearance of IgM antibodies to herpes simplex virus in the third study, laboratory markers of parvovirus infection. The predictive model created has accuracy of 92% and 94% (at three surveys) for prognosis of CI’s risks. It is shown that the predictive model based on the results of double and single survey is considerably less accurate – 85%. Conclusion: It is necessary for pregnants to be examined for CI’s markers in each trimester for effective prediction of probability of a CI. Reliable relationship with congenital infections was proved only to a combination of factors, combined into groups based on their statistical significance, confirming the need for an integrated dynamic examination of pregnant women. The high incidence of laboratory markers of parvovirus infection demonstrates the need for the inclusion of the infectious pathology in the list of pregnant mandatory screening.